Digital liaisons virtual uncommons: Creating knowledge, enhancing lives via digital libraries. Issue 1 (27th December 2016) - Cunningham, Christopher A; Grguric, Ekatarina; Gamble, Alyson
ABSTRACT: Digital libraries are uniquely poised as environments for knowledge creation and life enhancement. Researchers are able to develop and utilize the virtual environment in compelling ways, including global engagement with people who are new to practicing information science. Virtual sessions and unconferences are two innovative ways to connect established practitioners with less experienced students and professionals in supportive, collaborative environments. By combining these two formats, we propose hosting a virtual uncommons that transcends geographical locations. The Digital Liaisons Virtual Uncommons (DLVU) will feature leaders in digital libraries who will act in a mentoring capacity by responding to questions posed by new information professionals. In the DLVU, innovative students and early career professionals will be able to connect with mentors in the field of digital librarianship. The virtual uncommons will be a space for informal mentoring and serendipitous networking. This session will feature a Twitter chat under the hashtag #SIGDLchats (OR #DL4Good) for LIS students and newly practicing professionals to connect with mentors in the field with a focus on the changing nature of modern librarianship. Mentors will be sought out beforehand and the session will be widely publicized to international LIS, IS, Archival, etc. I‐*, programs.